Պերճ Զեյթունցյանի արձակը հայ գրաքննադատության գնահատմամբ - Սարգսյան, Տաթևիկ
О произведениях Перча Зейтунцяна в армянской литературной критике в основном было написано по поводу полемики, обсуждая проблемы соотношения нацианального и общечеловеческого, факта и искусства. В нашей статье мы собрали все литературные отклики, статьи и общие положения полемики о прозе Перрча Зейтунцяна, а также обосновывали необходимость структурального и сравнителного анализа произведении Зейтунцяна. In Armenian literature criticism about the creations of Perch Zeytuntsyan is was written generally in occasion of polemic about the attitudes of national and universal human, the fact and the art. In our article we’ve summarized the issues, literature responses and fundamental thesises about Perch Zeytuntsyan’s prose, also we’ve proved the need of structural and comparative analysis of Zeytuntsyan’s works.
Keywords: Գրականագիտություն